Reflections on qualitative research: Lessons learned to ensure research integrity - Deidré Pretorius; Khyati Dama; Michelle Erasmus (South African Family Practice)
This article focusses on teaching medical students qualitative research in a practical setting of a study about sexual health. Insufficient training, research deviating from the proposal and context-related factors contributed to compromising trustworthiness of the study. The article provides a background to the study and reflects on factors that contributed to the breach of research integrity after the research supervisor questioned the credibility of findings. A semi-structured interview schedule was used, and data analysis exposed flaws. The team used Jasper’s reflective cycle to change a crisis into a learning opportunity. The action plan triggered round two of data collection, followed by another reflective cycle.